KENDALA YANG DIHADAPI GURU DIMASA PANDEMI DI TK SATU ATAP COMOK SINAR JAYA (Tadzkirah : Jurnal Pendidikan Dasar, 2021)
ABSTRAK The purpose of this research is to define getting information on the obstacles to the teaching process faced by teachers as a result of the COVID 19 pandemic. This research uses exploratory case studies and a research approach using qualitative case studies to obtain information on the constraints and consequences of the COVID 19 pandemic. What teachers do in One Roof Kindergarten schools in this study the respondents were three teachers, two guardians and two students. The results of this study are the obstacles faced by parents, namely having to set aside money to buy internet data, children who are difficult to study at home, easily bored and lazy to learn, the obstacles faced by teachers are that not all parents can use technology, signal difficulties and often parents who do not patiently yelling and hitting their children when the child does not want to learn the obstacles faced by the child cannot play to develop child development asper by using game tools provided by the school to develop children's development, unable to play withfriends of the same age or age.